Picturing technology in China : from earliest times to the nineteenth century - Golas, Peter J. (Hong Kong University Press, 2015)
Although the history of technological and scientific illustrations is a well-established field in the West, scholarship on the much longer Chinese experience is still undeveloped. This work by Peter Golas is a short, illustrated overview tracing the subject to pre-Han inscriptions but focusing mainly on the Song, Yuan, Ming, and Qing dynasties. His main theme is that technological drawings developed in a different way in China from in the West largely because they were made by artists rather than by specialist illustrators or practitioners of technology. He examines the techniques of these artists, their use of painting, woodblock prints and the book, and what their drawings reveal about changing technology in agriculture, industry, architecture, astronomical, military, and other spheres. The text is elegantly written, and the images, about 100 in all, are carefully chosen. This is likely to appeal to both scholars and general readers.